The sword of summer - Riordan, Rick (Riordan, Rick. Magnus Chase and the gods of Asgard, 2015)
"Magnus Chase has always been a troubled kid. Since his mother's mysterious death, he's lived alone on the streets of Boston, surviving by his wits, keeping one step ahead of the police and the truant officers. One day, he's tracked down by an uncle he barely knows-a man his mother claimed was dangerous. Uncle Randolph tells him an impossible secret: Magnus is the son of a Norse god. The Viking myths are true. The gods of Asgard are preparing for war. Trolls, giants and worse monsters are stirring for doomsday. To prevent Ragnarok, Magnus must search the Nine Worlds for a weapon that has been lost for thousands of years. When an attack by fire giants forces him to choose between his own safety and the lives of hundreds of innocents, Magnus makes a fatal decision. Sometimes, the only way to start a new life is to die ..."--Publisher.